2017
DOI: 10.14348/molcells.2017.0026
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Proliferates Vaginal Epithelium through RhoA Expression in Postmenopausal Atrophic Vagina tissue

Abstract: Postmenopausal atrophic vagina (PAV) is the thinning of the walls of the vagina and decreased lugae of the vagina. PAV is caused by decreased estrogen levels in postmenopausal women. However, the harmful effects of hormone replacement therapy (HRT) have resulted in considerable caution in its use. Various estrogen agonist treatment options are available. Vitamin D is influences the regulation of differentiation and proliferation of various cells, especially tissues lining stratified squamous epithelium, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Vitamin D plays a role in the differentiation and proliferation of various cells [ 13 ]. Some previous studies reported changes in serum 25-hydroxyvitamin D3 ([25(OH)D3] or [25(OH)D]) during the luteal phase [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D plays a role in the differentiation and proliferation of various cells [ 13 ]. Some previous studies reported changes in serum 25-hydroxyvitamin D3 ([25(OH)D3] or [25(OH)D]) during the luteal phase [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, it could promote the barrier integrity of the vaginal epithelium. Vitamin D was shown to upregulate genes encoding epithelial cell junction proteins and stimulated proliferation of the vaginal epithelium 35,36 . Furthermore, two studies found that postmenopausal women receiving vitamin D treatment had increased numbers of superficial vaginal epithelial cells compared to women not receiving treatment, and that this increase was accompanied by decreases in vaginal pH 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The aging cells were induced by 10 mg/mL d -gal for 48 h . Then, the aging cells were incubated with 1 μM T16 collagen or estrogen (E2; Sigma-Aldrich Corp.) in different groups . To analyze their viabilities, the cells (5000/well) were seeded in a 96-well plate and their OD (optical density) values at 450 nm were measured at 0, 24, 48, 72, and 96 h using a cell counting kit (CCK-8, Boster, Wuhan, China) on a microplate reader.…”
Section: Methodsmentioning
confidence: 99%